تطور الحركة التعليمية في الدولة العثمانية 1876- 1909م (دراسة تاريخية) (Journal of the College of Basic Education, 2024)
The educational movement occupied a special place in the history of the Ottoman Empire during the reign of Sultan Abdul Hamid II (1879-1909). He succeeded in bringing a new and advanced educational life to the Ottoman Empire and its affiliated states, after the state had witnessed an era of backwardness and ignorance that lasted for many years until it was launched. It was called (the sick man), so Sultan Abdul Hamid II decided to adopt a modern educational policy based on carrying out comprehensive reform in the educational movement, through the establishment of many schools, institutes and colleges, in addition to adopting curricula that keep pace with civilizational development, thus creating a qualitative shift in the educational movement. At a time when the state was in dire need of it due to its lag behind civilization that had been progressing since the middle of the nineteenth century, and realizing that education was the most effective means of building the progress of nations, Sultan Abdul Hamid II paid exceptional attention to the educational movement, in order to build the state on modern foundations.Accordingly, the research is divided into three main sections.The first section: The beginnings of education in the Ottoman EmpireThe second topic: The Ottoman educational policy in light of the issuance of the Ottoman Banking Law.The third topic: Education during the reign of Sultan Abdul Hamid II